2009
DOI: 10.1097/01.fch.0000342838.05607.63
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Latinas Aging With Disabilities

Abstract: Latinas with disabilities report greater levels of disablement than Non-Hispanic, White women with disabilities. Over the life course, Latinas experience increased numbers of functional limitations, more difficulties with activities of daily living, and more unemployment due to impairments. The reasons for this health disparity are unclear. The purpose of this paper is to explore the empirical evidence surrounding health disparities in disablement among Mexican American women. From this exploration, recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…There are various factors that may influence any part of the disablement process (Verbrugge & Jette, 1994). Pain can be considered a biological factor that can influence disablement outcomes (Harrison, 2009). In the current study we sought to understand if the biological factor of pain was associated with ADL disability in older African American women and/or men.…”
Section: Introductionmentioning
confidence: 99%
“…There are various factors that may influence any part of the disablement process (Verbrugge & Jette, 1994). Pain can be considered a biological factor that can influence disablement outcomes (Harrison, 2009). In the current study we sought to understand if the biological factor of pain was associated with ADL disability in older African American women and/or men.…”
Section: Introductionmentioning
confidence: 99%
“…As women age, cultural expectations and response behaviors may change (Harrison, 2009). The description of Liliana’s pain experience showed that her life course experiences and emotions significantly impacted the intensity of her pain and decisions on how to cope with her pain.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a study examining life course stressors and their influence on elderly Mexican migrants, Montes De Oca, Garcia, Saenz, and Guillen (2011) reported that many migrants reported unequal work conditions, isolation and lack of health care throughout their lives negatively impacted their mental and physical health in later life. Harrison (2009) recommended examining psychological, biological, cultural and social factors from a life course perspective in Hispanic women with disabilities. Stressors that have accumulated throughout a person’s life can have strong implications on health outcomes and healthcare needs in later life (Zoltnick, Tam, & Soman, 2012; Hass, Kruger, & Rohlfsen, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is essential that nurse researchers examine biological data in groups such as older women with mobility limitations because it can provide further knowledge on disability and health outcomes in late life (Harrison, 2009; Kang, Rice, Park, Turner-Henson, & Downs, 2010; Whitfield, Angel, & Wong, 2011) that can be essential for the development of appropriate health care treatments and interventions (Nosek, 2000). For example, understanding cortisol levels and stress may reveal information about the daily life of older adults with mobility limitations (Kalpakjian, Farrell, Albright, Chiodo, & Young, 2009) and examining the lengths of telomeres may provide information on disability risk (Risques et al, 2010).…”
mentioning
confidence: 99%
“…These women have unique needs that are important to anticipate before collecting biological data in the community. For instance, the women may experience fatigue (Harrison & Stuifbergen, 2001), pain (Harrison, 2009), and have limited dexterity (Crentsil, Ricks, Xue, & Fried, 2010; Feeny et al, 2012) that may present difficulties when collecting biological samples. Hence, within the context of a pilot study designed to investigate the relationships between biological influences (telomere length, cortisol, and C-reactive protein [CRP]) and psychosocial influences (pain, depression) on perceptions of disablement (impairment, function and disability) in women aging with mobility limitations, the authors sought to evaluate the need for accommodations when recruiting and conducting biological research.…”
mentioning
confidence: 99%